Assessment of the greenness of an organization: bibliometric study and strategic document analysis - Skačkauskienė, Ilona; Smirnova, Juliana (Business, Management and Economics Engineering, 2023)
Purpose – the purpose of the research is to examine possibilities of practical implementation of the guidelines provided in the publicly available strategic documents and initiatives to assess the current situation of an organization in the aspect of greenness. Research methodology – methods of analysis of the scientific literature, review of strategic documents, bibliometric analysis, and critical evaluation have been applied. Findings – the need to develop guidelines to assess the greenness of an organization in the scope of the entire organization was identified. Research limitations – the limited selection of documents for the analysis, because the search of strategic documents relevant to the analyzed topic performed among the publicly available sources in English. Further studies could incorporate an analysis of guidelines and good practices used in different countries presented in other languages. Practical implications – the results of the research can be used to justify the need to develop guidelines to assess greenness at the scope of the entire organization. Originality/Value – can be defined by examination guidelines provided in the strategic documents from the perspective of practical applicability in organizations.